EPCO-32. AN EPIGENETIC SINGLE-CELL ATLAS OF IDH-MUTANT GLIOMA REVEALS THE ROLE OF ATRX IN SHAPING TUMOR COMPOSITION. (9th November 2020) - Babikir, Husam; Wang, Lin; Shamardani, Karin; Sudhir, Sweta; Kohanbash, Gary; Aghi, Manish; Philips, Joanna; Diaz, Aaron
Abstract: Recent single-cell RNA-sequencing studies have identified a hierarchy of cell types that is common to all isocitrate dehydrogenase (IDH) -mutant gliomas. This finding is somewhat paradoxical since the genetic differences between IDH-mutant astrocytomas and IDH-mutant oligodendrogliomas are prognostic, predictive of therapeutic response, and correlated with differences in immune infiltrates. To integrate these disparate findings, we constructed a single-cell atlas of 28 human IDH-mutant primary untreated grade-II/III gliomas. All specimens were profiled by single-cell assay for transposase-accessible chromatin, with additional cohorts profiled via single-cell RNA-sequencing and single-cell spatial proteomics. We determined the cell-type specific differences between IDH-mutant gliomas in transcription-factor utilization, associated targeting and cis-regulatory grammars. To elucidate the role of the chromatin remodeler ATRX (inactivated in over 86% of IDH-mutant astrocytomas) in shaping observed differences in open chromatin, we knocked out ATRX in an immunocompetent model of IDH-mutant glioma and subjected murine tumors to single-cell profiling. We found: 1. ATRX-deficient, IDH-mutant human and murine gliomas both upregulate an astrocytic regulatory program driven by Nuclear Factor I genes and downregulate an oligodendrocytic program driven by basic helix-loop-helix transcription factors. 2. Both human and mouse ATRX-deficient, IDH-mutant gliomas up-regulate genes that promote myeloid-cell chemotaxis and both have significantly higher percentages of myeloid-derived immune-suppressive cells than controls; 3. A transcription-factor program is conserved between human and murine ATRX-deficient tumors that shapes glial identity and promotes local immunosuppression. These studies elucidate how IDH-mutant gliomas from different subtypes can have distinct cellular morphologies and tumor micronenvironments despite a common lineage hierarchy.